2019
DOI: 10.1101/738500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wolbachiainfection in Argentinean populations ofAnastrepha fraterculus sp1: preliminary evidence of sex ratio distortion by one of two strains

Abstract: Background: Wolbachia, one of the most abundant taxa of intracellular Alphaproteobacteria, is widespread among arthropods and filarial nematodes. The presence of these maternally inherited bacteria is associated with modifications of host fitness, including a variety of reproductive abnormalities, such as cytoplasmic incompatibility, thelytokous parthenogenesis, host feminization and male-killing. Wolbachia has attracted much interest for its role in biological, ecological and evolutionary processes as well as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 117 publications
(98 reference statements)
0
2
0
2
Order By: Relevance
“…These two A. fraterculus lines were also purified from the A. fraterculus IGEAF strain, considering the Wolbachia strain they harbor (wAfraCast1_A and wAfraCast2_ A, respectively) [72]. Each strain was maintained for 70 generations under laboratory conditions.…”
Section: Af-cast-1 and Af-cast-2 Strainsmentioning
confidence: 99%
“…These two A. fraterculus lines were also purified from the A. fraterculus IGEAF strain, considering the Wolbachia strain they harbor (wAfraCast1_A and wAfraCast2_ A, respectively) [72]. Each strain was maintained for 70 generations under laboratory conditions.…”
Section: Af-cast-1 and Af-cast-2 Strainsmentioning
confidence: 99%
“…Early studies in the Mexican fruit fly, Anastrepha ludens (Loew) were carried out to evaluate resistance or sensitivity to a variety of antibiotics in bacteria isolated from this same species ( Kuzina et al, 2001 ) and to test the attractive effect of metabolites produced by bacteria on A. ludens ( Martínez et al, 1994 ). In addition, studies have determined the presence of Wolbachia in Anastrepha species ( Mateos et al, 2020 ), including guava fruit fly, A. striata ( Martínez et al, 2012 ), West Indian fruit fly, A. obliqua ( Mascarenhas et al, 2016 ), South American fruit fly, A. fraterculus ( Conte et al, 2019 ) and sapote fruit fruit fly, A. serpentina ( Coscrato et al, 2009 ). On the other hand, studies have revealed that the gut bacterial community in flies consists mainly of species of the Enterobacteriaceae family ( Noman et al, 2020 ), and that these microorganisms may be involved in nitrogen fixation, nutrition and insect fitness, including mating behavior and sexual competitiveness, reproductive success, longevity, improve the males fitnnes ( Gavriel et al, 2011 ; Hamden et al, 2013 ; Andongma et al, 2015 ; Khaeso et al, 2017 ; Yuval, 2017 ; Juárez et al, 2019 ), protection against pathogens and detoxification ( Ben-Yosef et al, 2015 ; Guo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar da incompatibilidade citoplasmática (IC), descrita por Laven (1967) ser uma das alterações reprodutivas causadas pela Wolbachia mais frequente entre os insetos (BOURTZIS et al, 2003) sua ocorrência parece estar vinculada tanto a certas características da linhagem da Wolbachia quanto também de seu hospedeiro ou, em outras palavras, não é possível assumir-se que a simples presença da bactéria produza o efeito IC. Linhagens de Wolbachia presentes em amostras de A. sp.1 da Argentina, diferentes da aqui descrita mostraram causar o fenótipo morte dos machos (male killing), enquanto outras mostraram causar o fenótipo IC em diferentes morfotipos do complexo fraterculus (CONTE et al, 2019;DEVESCOVI et al, 2019). Além disso, a incidência da IC é possivelmente também dependente do tempo da associação de uma dada linhagem com seu hospedeiro (TURELLI, 1994).…”
Section: Discussionunclassified
“…fraterculus na Argentina. Os resultados de cruzamentos sugeriram que a linhagem wAfraCast1 poderia estar induzindo a morte de machos (CONTE et al, 2019). Em outro estudo, IC intraespecífica (unidirecional) foi demonstrada em A. sp.1 aff.…”
Section: Incompatibilidade Citoplasmática (Ic) é O Fenótipo Mais Comum Induzido Porunclassified